A femoral clamp to reduce soft tissue artefact: accuracy and reliability in measuring three-dimensional knee kinematics during gait - Ding,Z; Gudel,M; Smith,SHL; Ademefun,RA; Bull,AMJ (Journal of Biomechanical Engineering, 2019)
The accurate measurement of full sixdegrees-of-freedom(DOFs) knee joint kinematics is prohibited by soft tissue artifact (STA), which remains the greatest source of error. The purpose of this study was to present and assess a new femoral clampto reduce STA at the thigh. It was hypothesised that the device can preserve the natural knee joint kinematics pattern and outperform a conventional marker mounted rigid cluster during gait. 6Six healthy subjects were askedto walk barefoot on level ground with a cluster marker set (cluster gait) followed by a cluster-clamp-merged marker set (clamp gait) and their kinematics wasmeasured using the clustermethod in clustergait and thecluster and clamp methodssimultaneouslyin clamp gait. Two operators performed the gait measurement. A six DOFs knee joint model wasdeveloped to enable comparison withthe gold standard knee joint kinematics measured using adual fluoroscopic imaging technique. One-dimensional paired t-tests were used to compare the knee joint kinematics waveforms between cluster gait and clamp gait. The accuracy was assessed in terms of the root mean square error, coefficient of determination and Bland-Altman plots. Inter-operatorreliability was assessed15usingthe intra-class correlation coefficient.The result showed that the femoral clamp did not change the walking speed andknee joint kinematicswaveforms. Additionally, clamp gait reduced the rotationand translation errorsin the transverse plane and improved the inter-operator reliabilitywhen compared to the rigid cluster method, suggesting amore accurate and reliable measurement of knee joint kinematics.